Factors related to self-medication in undergraduate nursing students: a scoping review - Guimarães Silveira, Hemelly Nogueira; Secoli, Silvia Regina; São-João, Thaís; Carrilho Menezes, Aline; de Oliveira, Flávia; Nunes Andrade , Silmara; Donizetti Trevisan, Danilo (Investigación y Educación en Enfermería, 2025)
Objective: The aim of this study was to map and summarize the extent and type of evidence related to self-medication among undergraduate nursing students. Method: A scoping review was conducted in accordance with the guidelines of the Joanna Briggs Institute. The guiding questions of the interviews were the following: 1) "What are the reasons/motivations and health conditions leading to self-medication behavior in nursing students?"; 2) "What are the sources of information involved in the decision-making process for self-medication?"; 3) "What medications are used in self-medication?"; 4) "What are the perceptions of risks and benefits of this behavior?"; 5) "What are the knowledge, beliefs/attitudes, and practices regarding self-medication?" The descriptors used were: "self-medication" AND "students, nursing" combined with their synonyms. A total of 55 articles were included from searches in the MEDLINE, Web of Science, Scopus, and Virtual Health Library databases, including gray literature. Results: The analysis of the studies resulted in ten categories characterizing the factors of self-medication: clinical conditions (n=52), reasons/motives (n=54), recall period (n=22), drug classes (n=54), sources of advice (n=53), perception of risks (n=47) and benefits (n=21), knowledge (n=27), beliefs and attitudes (n=27), and practices (n=20). Conclusion: This study showed that clinical, socioeconomic, and behavioral factors are common themes described in the literature on self-medication among undergraduate nursing students. There are opportunities, especially in training, to improve self-medication practices and patient safety among future nurses.